2015
DOI: 10.1097/bcr.0000000000000142
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intravenous Vitamin C on Point-of-Care Glucose Monitoring

Abstract: Ascorbic acid (vitamin C) decreases systemic inflammation and lowers fluid requirements after thermal injury; therefore it has been adopted in many burn centers as an adjunct to resuscitation. However, recent concerns have been expressed over clinically significant hypoglycemic events caused by vitamin C interference with the point-of-care (POC) glucose measurements. This case series presents a direct comparison of POC and laboratory reference glucose values in the patients receiving vitamin C infusion. Vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 29 publications
(16 reference statements)
1
50
1
Order By: Relevance
“…Multiple cases of inaccurate POC BG level measurements in patients receiving high‐dose IV vitamin C were reported, but none of these patients had sepsis. The indications for vitamin C in these studies included malignancy, diabetic retinopathy, and burn resuscitation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple cases of inaccurate POC BG level measurements in patients receiving high‐dose IV vitamin C were reported, but none of these patients had sepsis. The indications for vitamin C in these studies included malignancy, diabetic retinopathy, and burn resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review of five patients receiving vitamin C demonstrated significantly higher mean POC BG levels (225 ± 71 mg/dl) compared with mean laboratory BG levels (138 ± 41 mg/dl) . Additionally, a case series involving seven burn patients reported a difference in POC BG and laboratory BG levels ranging from 10–200 mg/dl . In some cases, the interference appeared to continue well beyond the discontinuation of vitamin C therapy …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An example of burn specific pharmacotherapy interfering with laboratory testing has been recently recognized during high dose ascorbic acid therapy. [3,4] During acute burn shock patients are resuscitated using the Parkland formula. [5,6] Patients who do not respond to standard resuscitation protocols are at risk of volume overload, which has been shown to lead to extremity or abdominal compartment syndrome as well as acute respiratory distress syndrome.…”
Section: Introductionmentioning
confidence: 99%